Pembangunan Sistem Informasi Akademik Yayasan XYZ Berbasis Web - Frederikus Winoto; Fedelis Brian Putra Prakasa; Findra Kartika Sari Dewi (Universitas Atma Jaya Yogyakarta, 2024)
The management of academic data at XYZ Foundation, which oversees kindergarten, elementary, middle, and high schools, is still conducted manually, resulting in issues such as unorganized data distribution, difficult access, and delayed information. To address these problems, a web-based academic information system was developed using the Laravel framework for the backend and React JS for the frontend, with MySQL as the database. This system is designed to manage various academic data, including student and teacher information, classes and class guardians, subjects, course enrollment, attendance, satisfaction surveys, and student e-reports. The research results indicate that this system successfully enhances the effectiveness and efficiency of academic data management and is well-received by the school staff, who find it extremely helpful. The system offers significant benefits in terms of time efficiency, process simplicity, and meeting the school's expectations. Pengelolaan data akademik di Yayasan XYZ, yang menaungi TK, SD, SMP, dan SMA, masih dilakukan secara manual, sehingga menimbulkan berbagai masalah seperti penyebaran data yang tidak terorganisir, akses yang sulit, dan keterlambatan informasi. Untuk mengatasi masalah ini, dibangunlah sebuah sistem informasi akademik berbasis web menggunakan framework Laravel sebagai backend dan React JS sebagai frontend, serta MySQL sebagai basis data. Sistem ini dirancang untuk mengelola berbagai data akademik termasuk data siswa, guru, kelas, mata pelajaran, presensi, survei kepuasan, dan e-rapor siswa. Hasil penelitian menunjukkan bahwa sistem ini berhasil meningkatkan efektivitas dan efisiensi pengelolaan data akademik, serta diterima dengan baik oleh pihak sekolah yang merasa sangat terbantu dengan adanya sistem ini, memberikan manfaat signifikan dalam efisiensi waktu, kemudahan proses, dan pemenuhan harapan sekolah.